Ultrastucture of Wolbachia are Found in Somatic and Reproductive Tissue of Drosophila simulans and D. melanogaster - ENDANG SRIMURNI KUSMINTARSIH (Indonesian Society for microbiology, 2011)
Ultrastructural observations shows Wolbachia in the testis of Drosophila melanogaster, where Wolbachia and cytoplasm are excluded from the mature sperm, and also found either in somatics and reproductive organ of D. simulans. Details of the ultrastructure of Wolbachia pipientis from the reproductive and somatic organs of D. melanogaster harbour Wolbachia-induce popcorn-effect and D. simulans harbour Wolbachia-induce cytoplasmic incompatibility are described as follows: the ultrastructure of Wolbachia in both of them were similar, distribution of Wolbachia in D. simulans was not restricted to the reproductive organs, they were also found in somatic tissues (muscle). Wolbachia can be present without causing detrimental effects. They are pleomorphic (rod shaped, elongate, oval or slightly bent). The size varies between 0.04 µm and 0.47 µm in diameter and between 0.26 µm and 1.2 µm in length. In a few cases Wolbachia seem to have been undergoing fission, but are still joint together by a vacuolar membrane. The microorganisms appear to have two membranes, a host membrane and a bacterial membrane. However, in some cases the microorganism seems to be surrounded by only one membrane, the possibility why only one membrane was visible might be due to loss during the embedding process